Peningkatan Kompetensi Guru Dalam Menyusun Perangkat Ajar Kurikulum Merdeka Melalui Supervisi Akademik di SMP Negeri 4 Jerowaru Kabupaten Lombok Timur - Turmuzi, Ahmad (Alpatih Harapan Semesta, 2023)
The problem in this school action research is that the competence of teachers at SMP Negeri 4 Jerowaru, East Lombok Regency, in compiling teaching materials for the independent curriculum is still very low. The purpose of this study was to improve the competence of teachers of SMP Negeri 4 Jerowaru, East Lombok Regency in preparing teaching materials for the independent curriculum in the first semester of the 2022/2023 academic year through academic supervision. The research was conducted from September 2022 to January 2023. The subjects in this study were 12 class VII subject teachers at SMP Negeri 4 Jerowaru, East Lombok Regency. This school action research is a qualitative research, which was conducted in two cycles. Each cycle consists of the stages of planning, implementing, observing and reflecting. Data analysis used a qualitative descriptive analysis technique by comparing the results of the initial conditions with the results of the first cycle and the results of the second cycle, which were obtained through collaborative academic supervision with colleagues with individual supervision techniques, which included supervision of teaching materials (documentation study) and academic supervision of class visits (observation). The results of the action (supervision) of cycle I, the level of teacher competency in compiling independent curriculum teaching tools is still relatively low, so it is necessary to carry out supervision again in cycle II.The results showed that there was an increase in the ability of class VII teachers at SMP Negeri 4 Jerowaru in making lesson plans significantly in the pre-cycle, cycle I and cycle II, namely an increase in the average percentage of the five aspects supervised, as follows: the number of teachers who collected all the tools teaching materials from 16.67% (pre cycle), 64.81% (cycle I) to 90.74% (cycle II), the overall quality of teaching materials from 12.25% (pre cycle), 52.78% (cycle I ) to 79.28% (cycle II), the quality of the flow of learning objectives (ATP) from 7.51 (pre-cycle), 47.71% (cycle I) to 78.97% (cycle II), the quality of teaching modules (RPP ) from 13.00% (pre-cycle) 48.96% (cycle I) to 78.12% (cycle II), and the suitability of learning planning with the implementation of the learning process becomes from 25.00 (pre-cycle), 83.33% (cycle I) to 100% (cycle 2). With a predicate of success from a less predicate or ≤70% in the pre-cycle and cycle I, it becomes an adequate predicate or is in the range of values of 71 – 80% in cycle II. Based on the background, problem formulation, and research results, the authors conclude that academic supervision can improve the competence of class VII teachers at SMP Negeri 4 Jerowaru in preparing teaching materials for the independent curriculum in semester I of the 2022/2023 academic year.